2022
DOI: 10.1186/s13019-022-02064-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the unplanned reoperation following surgical treatment of pulmonary tumor

Abstract: Background In this study, we aimed to summarize the extremely important lesson and experience in the whole process of surgical treatments of lung tumors for the benefit of steps taken to prevent against unplanned reoperation. Methods Demographical and clinical information of 7732 patients were retrospectively retrieved and reviewed, who were diagnosed with pulmonary tumor and underwent surgical treatments from January 2016 to March 2021. Those pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, Wang et al [ 12 ] stated that lymphatic vessel treatment with energy devices is insufficient to prevent chyle leakage. Furthermore, several studies reported chylothorax following endoscopic lung or esophageal cancer resection using certain energy devices; therefore, such devices are not completely reliable [ 13 , 14 ]. Zhang et al [ 15 ] recently reported the usefulness of pedicled omohyoid flap coverings in preventing postoperative lymph node or chyle leakage.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wang et al [ 12 ] stated that lymphatic vessel treatment with energy devices is insufficient to prevent chyle leakage. Furthermore, several studies reported chylothorax following endoscopic lung or esophageal cancer resection using certain energy devices; therefore, such devices are not completely reliable [ 13 , 14 ]. Zhang et al [ 15 ] recently reported the usefulness of pedicled omohyoid flap coverings in preventing postoperative lymph node or chyle leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Reoperations are essential interventions for managing severe complications that may arise after surgical procedures. They are rare, but they impose an additional burden on patients and are associated with higher morbidity and mortality rates [ 5 , 7 ]. Our findings corroborate those of previous studies that reported unplanned reoperations as predictors of prolonged hospital stays, increased complications, and reduced short-term survival rates [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al reported that pleural adhesion separation surface and lymph node dissection surface were more prone to bleeding [ 17 ]. Moreover, many studies found unidentified bleeding sites in a large percentage of their cohort [ 6 , 7 ]. Therefore, we recommend careful inspection of all potential bleeding sources before closing the incision, especially the stumps of pulmonary and bronchial vessels, the pulmonary stapling line, and the lymph nodes dissection surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation